EFFECT OF DRIED WHOLE PLANT POWDER OF LEPTADENIA RETICULATA (RETZ.) WIGHT & ARN. AND PLUCHEA LANCEOLATA C.B. CLARKE ON PHAGOCYTOSIS AND RESPIRATORY BURST BY HUMAN POLYMORPHONUCLEAR NEUTROPHILS (IN VITRO STUDY) - DR. VIDYA DIGHE; SAIKAT S. MALLICK; HINA Q. SHAIKH (International Journal of Pharma and Bio Sciences, 2014)
In the present study, the effects of hydroalcoholic extract of whole plant powder of Leptadenia reticulata (Retz.) Wight & Arn. and Pluchea lanceolata (DC.) C.B. Clarke was explored on the respiratory burst in Polymorphonuclear Neutrophils (PMNs), as compared to a known stimulant PMA (Phorbol 12-myristate 13-acetate). Prior to the in vitro tests, the viability of the PMNs was assessed using the Trypan blue dye exclusion test. The formation of various Reactive Oxygen Species (ROS) was measured by performing in vitro assays viz. Phagocytosis of Candida albicans, Nitro blue Tetrazolium (NBT) assay and Nitric oxide (NO) assay. The studied concentration of of hydroalcoholic extract of whole plant powder of Leptadenia reticulata (Retz.) Wight & Arn. and Pluchea lanceolata (DC.) C.B. Clarke were 50, 100, 200, 400mg/ml. An increase in the respiratory burst at all the studied concentrations was observed in all the assays indicating its immunostimulating effect